2020
DOI: 10.7818/ecos.1977
|View full text |Cite
|
Sign up to set email alerts
|

Variation of uropygial gland volume and malaria infection between urban-rural environment in the house sparrow

Abstract: Autores. Editado por la AEET. [Ecosistemas no se hace responsable del uso indebido de material sujeto a derecho de autor] El volumen de la glándula uropigial y la infección por malaria varía entre hábitats urbano-rural en el gorrión común

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…Finally, it has been shown that individuals in better conditions exhibit faster feather growth [ 41 , 103 ]. Because birds with better body conditions normally produce larger uropygial glands [ 45 , 70 , 116 , 117 ], a positive relationship between uropygial gland size and feather growth rate could be predicted. However, we did not observe any relationship between the feather growth rate and the size of the uropygial gland.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been shown that individuals in better conditions exhibit faster feather growth [ 41 , 103 ]. Because birds with better body conditions normally produce larger uropygial glands [ 45 , 70 , 116 , 117 ], a positive relationship between uropygial gland size and feather growth rate could be predicted. However, we did not observe any relationship between the feather growth rate and the size of the uropygial gland.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the uropygial secretions of nestling hoopoes also include bacterial symbionts that produce antimicrobials [ 136 , 137 , 138 ] and repellents for mosquitoes and biting midges [ 113 ]. Associations between characteristics of the uropygial gland and the risk of parasitism [ 139 , 140 , 141 ], as well as symbiotic bacteria living in the uropygial gland [ 17 , 142 , 143 , 144 ], are now described in phylogenetically distant bird species. Thus, the beneficial effects of uropygial secretions for birds may be mediated by microbial symbionts.…”
Section: Beneficial Effects Of the Microbiome In Relation To Parasitism And Predationmentioning
confidence: 99%
“…No obstante, otros factores ambientales también jugarían un papel primordial para los patrones de infección en las aves en términos, por ejemplo, de prevalencia, riqueza y diversidad de parásitos, lo que favorece la necesidad de desarrollar estudios de la ecología de transmisión de parásitos en diversos ecosistemas como los abordados aquí, desde latitudes extremas del planeta (Cuevas et al 2020), a ambientes insulares de Macaronesia (Illera y Perera 2020) o zonas áridas como el desierto de Tabernas en Almería (Veiga y Valera 2020). Estos estudios también deben considerar los escenarios de cambio global, incluyendo aspectos tratados en este volumen como son los procesos de urbanización (Magallanes et al 2020) y cambio climático (García del Río et al 2020), que podrían alterar estas complejas interacciones entre aves, vectores y patógenos, afectando su dinámica de transmisión en ecosistemas naturales (Møller 2010;Garamszegi 2011;Møller et al 2013).…”
unclassified